2002
DOI: 10.3201/eid0807.010471
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Distribution, and Host Range ofPeste des petits ruminants virus, Turkey

Abstract: Peste des petits ruminants virus (PPRV, genus Morbillivirus), which causes a severe disease in sheep and goats, has only recently been officially declared to be present in Turkey. We carried out a study to determine the prevalence, distribution, and host range of PPRV in Turkey. A total of 1,607 animals, reared in 18 different locations, were monitored for the presence of antibodies to PPRV and the related virus of large ruminants, Rinderpest virus (RPV). Only two farms had animals that were free of antibody r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
124
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(140 citation statements)
references
References 14 publications
12
124
4
Order By: Relevance
“…The last reported cases of rinderpest were in 1991, and Turkey was declared rinderpest free by the OIE in 2003. In the following years serological virus detection and immunohistochemical studies carried out in different regions of Turkey indicated the presence of PPR virus infection in all regions of Turkey (Alçığır et al, 1996;Tatar and Alkan, 1999;Özkul et al, 2002;Yener et al, 2004;Yeşilbağ et al, 2005;Albayrak and Alkan, 2009;Sağlam and Temur, 2009). After the first detection of PPR in Turkey, rinderpest vaccine was used for control of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The last reported cases of rinderpest were in 1991, and Turkey was declared rinderpest free by the OIE in 2003. In the following years serological virus detection and immunohistochemical studies carried out in different regions of Turkey indicated the presence of PPR virus infection in all regions of Turkey (Alçığır et al, 1996;Tatar and Alkan, 1999;Özkul et al, 2002;Yener et al, 2004;Yeşilbağ et al, 2005;Albayrak and Alkan, 2009;Sağlam and Temur, 2009). After the first detection of PPR in Turkey, rinderpest vaccine was used for control of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Reverse transcriptase polymerase chain reaction (RT-PCR), a molecular diagnostic test based on amplification of the gene target offers a new strategy for diagnosis of PPRV, and is more sensitive than other tests. RT-PCR also offers the possibility of analysing the relationship between different PPRV strains for epidemiological studies (Shaila et al, 1996;Ozkul et al, 2002;Kwiatek et al, 2007;Wang et al, 2009;Balamurgan et al, 2010). Although RT-PCR overcomes the limitations of conventional tests, the sensitivity varies depending on the primer used and the gene targeted.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first description of PPR in the Ivory Coast (Gargadennec and Lalanne, 1942), infection has been seen in Africa, the Arabian Peninsula, the Middle East, and Southeast Asia (Taylor, 1984;Abu Elzein et al, 1990;Shaila et al, 1996;Ö zkul et al, 2002). In Turkey, PPRV infection has been well documented in sheep, goats, and cattle (Tatar and Alkan, 1999;Ö zkul et al, 2002;Albayrak and Alkan, 2009), but there are few data from wild ungulates.…”
mentioning
confidence: 99%
“…Since the first description of PPR in the Ivory Coast (Gargadennec and Lalanne, 1942), infection has been seen in Africa, the Arabian Peninsula, the Middle East, and Southeast Asia (Taylor, 1984;Abu Elzein et al, 1990;Shaila et al, 1996;Ö zkul et al, 2002). In Turkey, PPRV infection has been well documented in sheep, goats, and cattle (Tatar and Alkan, 1999;Ö zkul et al, 2002;Albayrak and Alkan, 2009), but there are few data from wild ungulates. There are restricted breeding areas for deer and endemic species such as the Konya Mouflon, Ovis gmelini anatolica; however, except for a few studies of gazelles, there is no literature on wildlife disease in captive or wild ruminants in Turkey (Gü r, 2008;Gü r et al, 2008).…”
mentioning
confidence: 99%